Phenothiazine-pyrene dyads: Photoinduced charge separation and structural relaxation in the CT state - Acar, Nursel; Kurzawa, Jana; Schneider, Siegfried; Clark, Timothy; et al. (Journal of Physical Chemistry A, 2003)
Electron donor-acceptor systems with phenothiazine linked directly to pyrene exhibit a dual emission in moderately and very polar solvents. Steady state and time-resolved fluorescence spectroscopy provide evidence that the "blue" and "red" emission bands originate from different species. Fluorescence excitation spectra show a similar appearance when the emission is monitored either in the red or blue spectral range, but they are slightly shifted against each other. This suggests that different isomers exist with a distinctly different photophysical behavior. Semiempirical (AM1/CI) molecular orbital calculations with a continuum solvent treatment have been used to establish the geometry of the two nearly isoenergetic stereoisomers and to calculate the properties of their excited Franck-Condon states. Geometry optimization of various excited states provides evidence for different internal relaxation coordinates for the phenothiazine-localized S-1 state and the charge transfer state S-6, on one hand, and the pyrene-localized S-2 (S-3) state, on the other hand. The relaxed geometries in the excited states of both isomers represent mirror images with identical properties. The different photophysical behavior of the two isomers is most likely caused by the different potential energy curves, or more precisely speaking, by different location and/or heights of the barrier along the reaction coordinates from the locally excited to the geometry-relaxed CT states.